Grenada : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in Grenada during the 1990s. The weak growth performance since 1990 reflected largely a continuous contraction in agricultural output, which declined each year from 1989 to 1993. The construction industry experienced a major contraction in 1992 owing to the sharp fall in public investment. In 1993, output declined in the mining and quarrying, construction, and manufacturing sectors as well as in agriculture. In contrast, the hotel and restaurant sector has exhibited strong growth since the late 1980s, with real value added growing by 13.8 percent, on average, each year since 1989.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet